Integration of Online Queue System and Electronic Medical Records to Improve Operational Efficiency in a Primary Clinic - Martin Agusta; Umi Narimawati; Bobi Kurniawan; Agus Riyanto; Raeni Dwisanty (Jesya, 2026)
This study aims to analyze the integration of an online queue system and Electronic Medical Records (EMR) as a managerial strategy to enhance operational efficiency at Klinik dan Laboratorium Pratama Muhammad Abdus Syafi (MAS). A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation review. The findings indicate that integrating the two digital systems significantly reduced patient waiting times, improved service flow, and minimized administrative duplication. From an operational management perspective, the integrated system optimized resource utilization, increased healthcare staff productivity, and strengthened data-driven decision-making. Digital transformation through system integration demonstrably improved operational efficiency and organizational performance stability. Successful implementation was strongly influenced by human resource readiness, information technology governance, and adequate infrastructure support. This study was conducted within a single institution using a qualitative approach, which limits the generalizability of the findings. This research provides empirical evidence on digital integration strategies in primary healthcare facilities and highlights digital transformation as a long-term managerial approach to achieving operational excellence and organizational sustainability.